Job Insecurity and Workplace Criminalities Among China Civil Engineering and Construction Corporations Employees Handling Iworo-Awori Road in Badagry, Lagos - Haruna Ishola Abdullahi; Olayemi Oluwadamilola Amosun (International Journal of Marketing & Human Resource Research, 2021)
The global economic meltdown impacts negatively on job security. The aftermath of job insecurity on employee are criminal acts like theft, vandalism, arson, kidnapping, assault, and battery. Therefore, this paper assesses Job Insecurity and Workplace Criminalities among China civil engineering and construction corporations` employees handling Iworo-Awori Road in Badagry Lagos State, Nigeria. The study adopted a quantitative research designs that is descriptive and cross-sectional in nature. Primary data were collected by administering 250 questionnaires on employees of Chinese Construction Companies handing Iworo-Ajido Road, and only 207 were returned. Therefore, the response rate was 82.8%, data were sourced secondarily through content analysis of edited textbooks, peer-reviewed journals, and online resources. It anchors on the strain theory by Robert King Melton and the conflict theory by Karl Marx. The sample size of the qualitative method was determined through a purposive sampling method. Findings revealed that 77.67% of the respondents were males while 16.50% were females, 5.83 % was non- response. In the test of hypothesis, the chi-square value 13.04 was greater than the table value of 8.08, hence the null hypothesis that there was no significant relationship between poor work conditions and employee involvement in criminal acts was rejected. This led to the acceptance of hypothesis that there is a significant relationship between poor work conditions and employee involvement in criminalities. The study recommends standardization of working conditions of construction workers in Nigeria through enabling laws and improvement of the general economic conditions in the country.